Multi-frequency study of the newly confirmed supernova remnant MCSNR J0512-6707 in the Large Magellanic Cloud - Kavanagh, P. J.; Sasaki, Manami; Bozzetto, L. M.; Points, S. D.; Filipovic, M. D.; Maggi, P.; Haberl, Frank; Crawford, E. J. (Astronomy & Astrophysics, 2015)
Aims: We present a multi-frequency study of the supernova remnant MCSNR J0512-6707 in the Large Magellanic Cloud. Methods: We used new data from XMM-Newton to characterise the X-ray emission and data from the Australian Telescope Compact Array, the Magellanic Cloud Emission Line Survey, and Spitzer to gain a picture of the environment into which the remnant is expanding. We performed a morphological study, determined radio polarisation and magnetic field orientation, and performed an X-ray spectral analysis. Results: We estimated the remnant's size to be 24.9 ( ± 1.5) × 21.9 ( ± 1.5) pc, with the major axis rotated 29° east of north. Radio polarisation images at 3 cm and 6 cm indicate a higher degree of polarisation in the northwest and southeast tangentially oriented to the SNR shock front, indicative of an SNR compressing the magnetic field threading the interstellar medium. The X-ray spectrum is unusual as it requires a soft ( 0.2 keV) collisional ionisation equilibrium thermal plasma of interstellar medium abundance, in addition to a harder component. Using our fit results and the Sedov dynamical model, we showed that the thermal emission is not consistent with a Sedov remnant. We suggested that the thermal X-rays can be explained by MCSNR J0512-6707 having initially evolved into a wind-blown cavity and is now interacting with the surrounding dense shell. The origin of the hard component remains unclear. We could not determine the supernova type from the X-ray spectrum. Indirect evidence for the type is found in the study of the local stellar population and star formation history in the literature, which suggests a core-collapse origin. Conclusions: MCSNR J0512-6707 likely resulted from the core-collapse of high mass progenitor which carved a low density cavity into its surrounding medium, with the soft X-rays resulting from the impact of the blast wave with the surrounding shell. The unusual hard X-ray component requires deeper and higher spatial resolution radio and X-ray observations to confirm its origin.
Keywords: ISM: supernova remnants; Magellanic Clouds; X-rays: ISM